Towards a study of antagonisms and political identities - Duárez Mendoza, Jorge Luis (2021)
This paper proposes a theoretical and methodological alternative for the analyses of contemporary political processes. Also, it relies on criticism of the predominant analytical perspective in Peruvian political science during the last years, which prioritized the political regime as an object of study. By recognizing politics relative autonomy, we propose to pay attention to antagonism and its operative role in the composition of political identities to study political processes. We argue that discourse analysis is a useful analytical tool for studying political antagonisms. This article contains three sections. In the first section, we develop our critic to the predominant analytical perspective of political science in Peru, showing its heuristic limits. In the second section, we present our theoretical framework. Also, we reflect on antagonism and differences between polity and politics from a post-foundational approach. In the third section, we focus on the theoretical-methodological aspects of our proposal based on discourse analysis. Finally, we present some conclusions about the importance of antagonism for political analysis, a theoretical-methodological scope of our proposal, and identified theoretical challenges for future research.